FACTORS INFLUENCING RELATIONSHIPS IN SAME-SEX PARENTING - Ofira, Citrin (E-Journal VFU, 2025)
The article "Factors Influencing Relationships in Same-Sex Parenting" offers in-depth insights into the elements shaping relationship quality and resilience among same-sex family. The academic focus on same-sex parenting relationships has gained momentum in recent years due to social, legal, and technological changes that underscore the complexities of family life within diverse family structures.
Keywords: development; relationships in same-sex parenting